PENGATURAN STANDARISASI KERINGANAN PENJATUHAN PIDANA TERHADAP JUSTICE COLLABORATORS DALAM KASUS PEMBUNUHAN BERENCANA - Bahri Yamin; Hilman Syahrial Haq; M. Taufik Rachman (Media Keadilan: Jurnal Ilmu Hukum, 2023)
There are three reasons why this research was conducted, namely: first, it has not been clearly regulated in the case of premeditated murder regarding whether or not it is permissible to assign Justice Collaborators to one of the perpetrators by the panel of judges. Second, the standardization of maximum and minimum crimes has not been regulated in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses. The three pros and cons of the criminal verdict against Barada Richard Eliezer. The legal issue is whether Justice Collaborators status can be given to participating actors in cases of premeditated murder? This journal uses normative research. The results of this study are: first, in cases of premeditated murder, justice collaborator status can be given to witness witnesses who cooperate by way of legal discovery by judges, using legal construction methods. Second, if there is a recommendation from the LPSK against a witness with the status of a witness collaborator in a case of premeditated murder, then the sentence will be reduced under the following conditions: a) When detained for the first time, the maximum penalty is 2 years. Minimum 1 year 6 months. b) during the extension of the detention period, the maximum penalty is 3 years, minimum 2 years. c) at the time of detention by the Prosecutor's Office, the threat is a maximum of 4 years, a minimum of 2 years and 6 months. d) at the time of becoming a defendant or convict, the maximum penalty is 5 years at least 3 years.